2019
DOI: 10.1002/etc.4545
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microplastic Ingestion on Survival of the Grass Shrimp Palaemonetes pugio (Holthuis, 1949) Challenged with Vibrio campbellii

Abstract: Recent research indicates that microplastic (<5 mm) ingestion may impact the immune function of marine and aquatic organisms at the tissue and cellular levels; however, their susceptibility to disease following exposure has not been directly investigated. The objective of the present study was to directly evaluate the impact of microplastic ingestion on the susceptibility of the grass shrimp Palaemonetes pugio to bacterial infection with Vibrio campbellii. Grass shrimp were exposed to one of several particle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Similarly, Gray and Weinstein ( 2017 ) tested the egestion of 11 different MPs with the estuarine shrimp P. pugio and observed no apparent trend towards a prolonged residence time of differently sized as well as shaped MPs. Likewise, the same species egested the majority of ingested PE spheres and PP fragments within 2 days (Leads et al 2019 ). Korez et al ( 2020 ) demonstrated that C. crangon egested the majority of PS beads after 24 to 48 h. However, they could not exclude the reentrance of MPs from feces due to coprophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Gray and Weinstein ( 2017 ) tested the egestion of 11 different MPs with the estuarine shrimp P. pugio and observed no apparent trend towards a prolonged residence time of differently sized as well as shaped MPs. Likewise, the same species egested the majority of ingested PE spheres and PP fragments within 2 days (Leads et al 2019 ). Korez et al ( 2020 ) demonstrated that C. crangon egested the majority of PS beads after 24 to 48 h. However, they could not exclude the reentrance of MPs from feces due to coprophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Saborowski et al ( 2019 ) demonstrated that the stomachs of P. varians were emptied from beads and fibers after 16–24 h. Bour et al ( 2020 ) support this observation since they demonstrated major and complete bead depuration in Artemia after 24 and 48 h, respectively. Leads et al ( 2019 ) showed that the egestion of different MP shapes is not affected in shrimps, which were previously injected with the bacterium Vibrio campbellii to increase their susceptibility to MPs. Taken together, our results are mostly in line with other publications and highlight that beads as well as fragments pass the shrimp’s gut.…”
Section: Discussionmentioning
confidence: 99%
“… Qiao et al, 2019 Palaemonetes pugio (Decapoda) Polyester (63–150 um) obtained from fabric PP (34–93 um) obtained from weathered marine rope 50,000 items/L; 96 h No effects on survival and bacterial infection (for polyester). Increased mortality (PP) Leads et al, 2019 Lumbricus terrestris (Opisthopora) Polyester (361–387 × 40 Ø um) obtained from cushion 0, 0.1 and 1.0% w /w microfibers for 35 days ALtered burrowing and feeding behaviour, molecular genetic biomarkers. Prendergast-Miller et al, 2019 Achatina fulica (Stylommatophora) PET (1257 × 76.3 Ø um) 0.01–0.71 g/kg; 28 days Reduction in food intake and excretion, damage in the gastrointestinal walls, oxidative stress.…”
Section: Potential Ecotoxicological Effectsmentioning
confidence: 99%
“…corals, with a 41% decrease in photochemical efficiency after 12 days [16]. Grass shrimp (Palaemonetes pugio) were exposed to either sediment, polyethylene spheres, polypropylene fragments, tire fragments, polyester fibers, or clean-water for 96 h at a nominal concentration of 50,000 particles/L before a bacterial challenge with V. campbellii [17]. Mortality was not observed in any of the exposures, and survival following the bacterial challenge was similar among shrimp exposed to particle-free water, sediment, polypropylene fragments, polyethylene spheres, tire fragments, and polyester fibers.…”
Section: Aquatic Effectsmentioning
confidence: 99%